Discover training issues - a need to be trained skill for the vocational teachers - Đỗ Mạnh Cường, (Journal of Technical Education Science, 2007)
The curent pedagogical content in technical teacher training is focusing on some teaching skills like writing syllabus, lesson planing, and teaching. Those are necessary but not enough to link VTE and industry. To connect closely training and employee using, the technical teachers must demonstrate their helpful to the enterprises. Therefore, they need to be trained about many other things among which detection of training problem is very important.